Краткий словарь по философии - Азаров Н. И.; Айзикович А. С.; Аникеев Н. П.; Анцыферова Л. И.; Арзаканьянц Ц. Г.; Афанасьев В. Г.; Баженов Л. Б. (Москва, Политиздат, 1982)
Авторы указаны в конце книги.